Epigenetic Control of Plant Response to Heavy Metal Stress: A New View on Aluminum Tolerance - Gallo-Franco, Jenny Johana; Sosa, Chrystian Camilo; Ghneim-Herrera, Thaura; Quimbaya, Mauricio (Frontiers in Plant Science, 2020)
High concentrations of heavy metal (HM) ions impact agronomic staple crop production in acid soils (pH ≤ 5) due to their cytotoxic, genotoxic, and mutagenic effects. Among cytotoxic ions, the trivalent aluminum cation (Al3+) formed by solubilization of aluminum (Al) into acid soils, is one of the most abundant and toxic elements under acidic conditions. In recent years, several studies have elucidated the different signal transduction pathways involved in HM responses, identifying complementary genetic mechanisms conferring tolerance to plants. Although epigenetics has become more relevant in abiotic stress studies, epigenetic mechanisms underlying plant responses to HM stress remain poorly understood. This review describes the main epigenetic mechanisms related to crop responses during stress conditions, specifically, the molecular evidence showing how epigenetics is at the core of plant adaptation responses to HM ions. We highlight the epigenetic mechanisms that induce Al tolerance. Likewise, we analyze the pivotal relationship between epigenetic and genetic factors associated with HM tolerance. Finally, using rice as a study case, we performed a general analysis over previously whole-genome bisulfite-seq published data. Specific genes related to Al tolerance, measured in contrasting tolerant and susceptible rice varieties, exhibited differences in DNA methylation frequency. The differential methylation patterns could be associated with epigenetic regulation of rice responses to Al stress, highlighting the major role of epigenetics over specific abiotic stress responses.